Survival and establishment in field of mangaba seedlings transplanted at different ages - Santos, Marcos Paulo dos; Siqueira, Ana Paula Silva; Garcia, Lismaíra Gonçalves Caixeta; Vasconcelos, Luís Henrique Costa; Souza, Eli Regina Barboza de (Comunicata Scientiae, 2018)
The propagation of mangaba (Hancornia speciosa Gomes) occurs mainly by seeds, a lower cost method that guarantees genotypic diversity. The great barrier is the lack of knowledge of the proper transplanting time of these seedlings. This way, the objective of this study was to evaluate the development of mangaba seedlings transplanted at different ages during the summer in Goiânia, Brazil. A randomized complete block design was used in a 2x4 factorial arrangement, with two mangaba subspecies (gardneri and cuiabenses) and four transplanting ages [45, 60, 75 and 90 days after sowing (DAS)], with four replications. Before transplanting, a destructive analysis was carried out on three plants of each subspecies to determine the biometric characteristics as a function of seedling age. The field evaluations initiated at120 DAS, evaluating monthly the seedling survival (%), plant height, stem diameter and number of live leaves per plant until 210 DAS. The biometric characteristics were not affected by the mangaba subspecies. The plant survival decreased linearly throughout the experimental period, regardless of the subspecies. The interaction age transplanting x DAS showed that at 210 DAS the seedlings transplanted later presented greater growth in height and number of live leaves. Regardless of the subspecies, the mangaba presents limitations for establishment in the field, and it is recommended the transplantio of seedlings with 90 days of age.